2019
DOI: 10.1016/s2542-5196(19)30085-3
|View full text |Cite
|
Sign up to set email alerts
|

Associations between daily air quality and hospitalisations for acute exacerbation of chronic obstructive pulmonary disease in Beijing, 2013–17: an ecological analysis

Abstract: Summary Background Air pollution in Beijing has been improving through implementation of the Air Pollution Prevention and Control Action Plan (2013–17), but its implications for respiratory morbidity have not been directly investigated. We aimed to assess the potential effects of air-quality improvements on respiratory health by investigating the number of cases of acute exacerbations of chronic obstructive pulmonary disease (COPD) advanced by air pollution each year. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
84
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(92 citation statements)
references
References 42 publications
7
84
1
Order By: Relevance
“…Possible explanations for this discrepancy include that the O 3 concentration in Ningbo City may be different from that in other regions, or that other air pollutants may interact with O 3 . Liang L et al analysed the association between dairy SO 2 , NO 2 , O 3 , CO, PM 10 and PM 2.5 and hospitalisations for acute exacerbation of COPD in Beijing from 2013 to 2017 and the results indicated that exposure-response association of NO 2 with COPD cases was linear, while the SO 2 , CO, PM 10 and PM 2.5 were nonlinear, no significance was found in O 3 with COPD incidence [43]. Liu C et al investigated the air pollution and daily mortality in 652 cities, the results demonstrated that exposure-response association of PM 2.5 with mortality was non-linear [26].…”
Section: Discussionmentioning
confidence: 99%
“…Possible explanations for this discrepancy include that the O 3 concentration in Ningbo City may be different from that in other regions, or that other air pollutants may interact with O 3 . Liang L et al analysed the association between dairy SO 2 , NO 2 , O 3 , CO, PM 10 and PM 2.5 and hospitalisations for acute exacerbation of COPD in Beijing from 2013 to 2017 and the results indicated that exposure-response association of NO 2 with COPD cases was linear, while the SO 2 , CO, PM 10 and PM 2.5 were nonlinear, no significance was found in O 3 with COPD incidence [43]. Liu C et al investigated the air pollution and daily mortality in 652 cities, the results demonstrated that exposure-response association of PM 2.5 with mortality was non-linear [26].…”
Section: Discussionmentioning
confidence: 99%
“…and disagreements were settled by consensus. The characteristics of the included studies [17][18][19][20] are shown in Tables S1, S2, and S3.…”
Section: Data Extractionmentioning
confidence: 99%
“…So far, four analyses have been conducted to quantify the association between short-term ambient ozone exposure and COPD hospitalizations [13][14][15][16] (Table S1): one was focused solely on East Asia [13], one was based on publications before 2008 [14], and the other two, conducted in 2015 [15] and 2016 [16], simply reported pooled risk estimates. Since then, several original investigations have been published [17][18][19][20]. In addition, a major issue has been raised regarding exposure to other air pollutants simultaneously, which may confound ozone-related effect estimates [21].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The incidence and mortality of COPD are increasing progressively year by year. 1,2 The incidence and mortality of COPD are increasing progressively year by year.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic obstructive pulmonary disease (COPD), featured by chronic and progressive dyspnea, is the leading cause of global disease burden. 1,2 The incidence and mortality of COPD are increasing progressively year by year. 3 According to report by the World Health Organization in 2017, COPD is anticipated to be the third largest death causes by 2030.…”
Section: Introductionmentioning
confidence: 99%